Low-Dose Gene Therapy for Murine PKU Using Episomal Naked DNA Vectors Expressing PAH from Its Endogenous Liver Promoter - Hiu Man Grisch-Chan; Andrea Schlegel; Tanja Scherer; Gabriella Allegri; Raphael Heidelberger; Panagiota Tsikrika; Marco Schmeer; Martin Schleef; Cary O. Harding; Johannes Häberle; Beat Thöny (Elsevier, 2017)
Limited duration of transgene expression, insertional mutagenesis, and size limitations for transgene cassettes pose challenges and risk factors for many gene therapy vectors. Here, we report on physiological expression of liver phenylalanine hydroxylase (PAH) by delivery of naked DNA/minicircle (MC)-based vectors for correction of homozygous enu2 mice, a model of human phenylketonuria (PKU). Because MC vectors lack a defined size limit, we constructed a MC vector expressing a codon-optimized murine Pah cDNA that includes a truncated intron and is under the transcriptional control of a 3.6-kb native Pah promoter/enhancer sequence. This vector, delivered via hydrodynamic injection, yielded therapeutic liver PAH activity and sustained correction of blood phenylalanine comparable to viral or synthetic liver promoters. Therapeutic efficacy was seen with vector copy numbers of <1 vector genome per diploid hepatocyte genome and was achieved at a vector dose that was significantly lowered. Partial hepatectomy and subsequent liver regeneration was associated with >95% loss of vector genomes and PAH activity in liver, demonstrating that MC vectors had not integrated into the liver genome. In conclusion, MC vectors, which do not have a defined size-limitation, offer a favorable safety profile for hepatic gene therapy due to their non-integration in combination with native promoters.